PENGEMBANGAN MEDIA SCRAPBOOK PADA MUATAN MATERI MAKNA PANCASILA DAN KEBERAGAMAN KELAS 3 SEKOLAH DASAR NEGERI 2 DASAN GERES - Hikmah Nurdian; Khairun Nisa; Muhammad Sobri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT The aim of this research is to determine the practicality of scrapbook media in PPKn class 3 material at SDN 2 Dasan Geres. This type of research is Research and Development (R & D) using the ADDIE model which has 5 stages, namely Analysis, Design, Development, Implementation, Evaluation. The data collection techniques used were media expert validation questionnaires and material expert validation questionnaires, as well as teacher and student response questionnaires. The validity and practicality of the Scrapbook media shows a percentage score of 90%, the validity and practicality of the material shows a percentage score of 96%, the results of the student response questionnaire to the scrapbook media get a percentage score of 88.62%, while the results of the teacher response questionnaire get a percentage score of 92%. Therefore, the Scrapbook media containing material on the meaning of Pancasila and diversity for class 3 at SDN 2 Dasan Geres is practical and can be used in the learning process for Civics subjects. ABSTRAKTujuan penelitian ini yaitu untuk mengetahui kepraktisan media scrapbook pada materi PPKn kelas 3 SDN 2 Dasan Geres. Jenis penelitian ini yaitu Research and Development (R & D) dengan menggunakan model ADDIE yang memiliki 5 tahapan yaitu Analysis (analisis), Design (desain), Development (pengembangan), Implementation (implementasi), Evaluation (evaluasi).Teknik pengumpulan data yang digunakan adalah Observasi, angket/kuesioner, wawancara, dan dokumentasi. Hasil analisis data tingkat kepraktisan media Scrapbook menunjukkan skor persentase 90%, kevalidan serta kepraktisan materi menunjukkan hasil skor persentase 96%, hasil angket respon siswa terhadap media scrapbook memperoleh skor persentase 88,62%, sedangkan hasil angket respon guru mendapatkan skor persentase 92%. Oleh karena itu media Scrapbook pada muatan materi makna Pancasila dan keberagaman untuk kelas 3 di SDN 2 Dasan Geres praktis dan dapat digunakan pada proses pembelajaran mata Pelajaran PPKn.